Chiral tectonics toward square planar tetranuclear Pd(ii) complexes: propagation of axial chirality through a long molecular axis. Issue 27 (11th June 2019) - Goto, Yutaro; Watanabe, Yutaka; Noboriguchi, Aoki; Yoshida, Jun; Mori, Shigeki; Sato, Hisako
Abstract : Tetranuclear Pd(ii )complexes were synthesized according to the molecular tectonics approach. A focus was how the elongation of a molecular axis affected the chiro-optical properties of a molecule with axial chirality. Abstract : An approach of molecular tectonics was applied to synthesize a tetranuclear Pd(ii ) complex with axial chirality, [{(Lt )Pd(ii )(taet)Pd(ii )}2 (tpret)] (Lt H = benzoylacetone (bzacH) or 2-naphthoylacetone (npacH), taetH2 = 1, 1, 2, 2-tetraacetylethane and tpretH2 = 1, 1, 2, 2-tetrapropanoylethane). As a first step, a two-handed tecton, [taetHPd(ii )]2 (tpret)], was synthesized. Next monomeric Pd(ii ) units were connected to both ends of the tecton to form a reactive tetranuclear intermediate, [{(hfac)Pd(ii )(taet)Pd(ii )}2 (tpret)] (hfacH = hexafluoroacetylacetone). Finally terminal hfac groups were replaced with the β-diketonato ligands having one or two bulky groups such as dibenzoylmethane (dbmH), bzacH and npacH. In the case of the symmetrically substituted ligand (dbm), the formed complex was achiral and its structure was determined by single crystal X-ray analysis. In the case of unsymmetrical ligands (bzac and npac), the complexes were axially chiral due to the vertical twisting of the terminal ligands. The complexes were optically resolved chromatographically on a chiral column. Their chiro-optical properties were investigated by means of electronic (ECD) and vibrational circular dichroism (VCD) spectroscopy. Notably the twisting relation between the two terminal ligands of the tetranuclear complexes influenced significantly chiral electronic properties, although they were separated by a distance longer than 3 nm.